ANALISIS KANDUNGAN MERKURI (Hg) PADA LIMBAH HASIL PENGOLAHAN EMAS DI GUNUNG NONA DESA WAPSALIT PULAU BURU - L S Sello; Abraham Mariwy; Nazudin Nazudin (Molluca Journal of Chemistry Education (MJoCE), 2020)
The research had been done to analyze the mercury (Hg) content on tailing the result of gold processing at Nona Mountain Wapsalit Village Buru Island. The dry sample was prepared by putting it into the oven at 400C temperatures in two days and then the wet destruction done to the sample. The Tailing was analyzed by using SSA – Cold Steam to get to know about the mercury (Hg) content. The result showed that the average mercury (Hg) content at the location I was 721,43 ppm and at the location II was 344,88 ppm. Thus, the results showed that tailing concentration at the location I had average mercury (Hg) content higher than at the location II